First record of male-male combat in the Yellow-bellied Puffing Snake Spilotes sulphureus (Wagler, 1824) - Araújo, Gabrieli [UNESP]; Ramalho, Renan [UNESP]; Almeida-Santos, Selma [UNESP] (Brill Academic Publishers, 2024)
Male ritual combat is an intraspecific agonistic interaction associated with competition for food, mating and territory and has been described for several neotropical snakes. Here, we provide the first record of male-male combat in Spilotes sulphureus in Brazilian Atlantic Forest based on one fortuitous videotaped encounter. Males remained partially coiled in a vertical position during combat and performed various displays (e.g., downward push, tumble, vertical display and orientation, dorsal hyperextension, pinning and lyre-shaped) including some that were also observed during defensive behaviour (e.g., gular inflation, neck S-coil and latero-lateral flattening). Our observations bring new information about the natural history of S. sulphureus and show that this species shares some aspects of male-male combat with other colubrids, including S. pullatus, but a more in-depth study is necessary to understand the reproductive biology of this species.
Keywords: agonistic interaction; Atlantic Forest; Colubridae; gular inflation display; Pseustes; reproductive behaviour